2007
DOI: 10.1258/135763307780908021
|View full text |Cite
|
Sign up to set email alerts
|

Telepaediatrics

Abstract: Telepaediatrics is becoming increasingly popular for several reasons, including improved access to specialist care in tertiary hospitals and savings in travel costs, especially to the families concerned. There are well known examples of clinical telepaediatric services in areas such as cardiology, fetal medicine, school health and psychiatry. In addition, there is an extensive telepaediatric service in Queensland, which currently provides about 1300 telepaediatric consultations per year. It is encouraging to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Literature shows that this form of teleconsultation reduces the number of traditional face-to-face consultations with a dermatologist [20-23]. In addition, a telemedicine approach has also been proven cost-effective in diabetes care and pediatrics [24,25]. In the field of palliative homecare however, few quantitative studies have been carried out [26-30].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that this form of teleconsultation reduces the number of traditional face-to-face consultations with a dermatologist [20-23]. In addition, a telemedicine approach has also been proven cost-effective in diabetes care and pediatrics [24,25]. In the field of palliative homecare however, few quantitative studies have been carried out [26-30].…”
Section: Introductionmentioning
confidence: 99%
“…Although a patient satisfaction study was not undertaken, other surveys have shown excellent patient support for telehealth consultation. [1][2][3][5][6][7][8][9][10][11][12][13][14]19 We received no complaints about adverse clinical outcomes from this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Rural sites in Queensland often have limited infrastructure and experience in managing paediatric emergencies. These sites are usually staffed by generalist doctors without specialist training in paediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…Leibniz, num capítulo das suas primeiras notas médico-fisiológicas "Como é que o animal pode ser incitado a agir por (estímulo de) objectos externos ou internos e pelos órgãos dos sentidos", conclui que "ab exigua causa magnus ori tur in animal motus" tal como quando se abre a torneira e sai um forte jorro de água, ou quando a chama do rastilho atinge a pólvora. 48 Constatou-se muito depois que o mecanismo de propagação do influxo nervoso se baseia no mesmo tipo de fenó meno que a despolarização e activação do músculo. 49 Está, evidentemente, em causa, a reacção química (tipificada em fenómenos de explosão, fermentação e ebulição) e o modelo ou representação do corpo fibroso ou fibrilar e o seu culminar na teoria do "corpo nervoso" na doutrina médica de William Cullen.…”
unclassified